Analysis Of Strategies for Strengthening the Online Game Industry Using an Industrial Cluster Approach - Liliani Suciasih; Sugeng Santoso (PT FORMOSA CENDEKIA GLOBAL, 2024)
Based on data, as one of the creative economy sectors, the game industry has much potential to boost the Indonesian economy. The total market value of the games industry in Indonesia is US 1.92 billion or 25 trillion rupiah. However, Foreign developers from Europe and the US dominate the games industry market in Indonesia, making Indonesia only able to contribute 0.49% of total revenue. This research aims to map Indonesia's game industry players, analyse its ecosystem's environmental determinants, and formulate effective industry development strategies. This qualitative research uses interview methods with key informants, observation, and literature study, with purposive sampling as a sampling technique. The results show that the core industry value chain of the game industry cluster consists of Game Developers and Game Publishers and is supported by Supply industries (hardware providers, HR, digital content, and financial services) and supporting industries (marketing, logistics, law, and networks). There are related institutions/institutions such as the Ministry of Tourism and Creative Economy, the Coordinating Ministry for Maritime and Investment Affairs, the Ministry of Communications and Informatics, the Ministry of Education and Culture, and the Indonesian Game Association. This industry is also related to animation, music, e-sports and tourism. This value chain ends with buyers. This research recommends concrete steps for relevant agencies to enhance the gaming industry ecosystem through human resource development, increasing access to financing, promotion and providing technological infrastructure. Collaboration across industries is expected to increase the global competitiveness and contribute significantly to the national creative economy.